Options and prospects for drug treatment of uterine fibroids - T. E. Samoylova; D. Zh. Maksutova (Медицинский совет, 2013)
The emergence of new techniques and methods that inhibit tumor growth and promote regression of symptoms is introducing new approaches to the management and care of patients with uterine fibroids, both in surgical and drug treatment.